A Cas-embedding strategy for minimizing off-target effects of DNA base editors - Yajing Liu (Nature Portfolio, 2020)
DNA base editors can display off-target effects on DNA and RNA. Here the authors embed the base editing enzymes in the middle of nCas9 to reduce these without impacting on-target editing.